Principal and expert agent - Malcomson, J (University of Oxford, 2004)
This paper analyses principal-agent contracts when the agent's action generates information not directly verifiable but used by the agent to make a risky decision. It considers a more general formulation than those studied previously, focusing on the impact on the decision made and the contract between principal and agent. It establishes a precise sense in which distorting decisions reduces the risk borne by a risk-averse agent and conditions under which implementing an optimal decision rule imposes no substantive restrictions on the contract. The paper also uses an application to bidding to supply a good or service to illustrate those results and derive additional ones. A risk-neutral agent with limited liability may optimally choose lower, less risky bids or higher, more risky bids, according to which relaxes the limited liability constraint. There are also natural conditions under which optimal contracts are monotone, possibly with flat sections, like stock option rewards.